PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR DESA (studi kasus:Pembangunan Jalan Desa Riung Kecamatan Cibal Kabupaten Manggarai Nusa Tenggara Timur) - Gonzaga, Yohana Apriliani Indarsi; Prabawati, Ni Putu Anik; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2023)
The case in this exploration is to detect out aspects related to community participation that can be discerned through murserbang conditioning to the evaluation stage, so the purpose of this study is to determine community participation in structure evolution in Riung desage, Cibal quarter, Manggarai quarter. This study uses a type of qualitative exploration with descriptive path. Sources of data exercised are primary data and secondary data. The fashion of arbitrating the snitchers in this study exercised intentional slice. Grounded on this exploration study utilizing the proposition of participation tallying to Mardikanto et al( 2013; 81). The effects of the study show off that community participation in desageage structure evolution( case study road construction in Riung Desageage, Cibal sub-district, Manggarai quarter) is relatively good, because the community provides backing in the shape of dynamism, and allowed, this shows that nearly all community ingredients see and are active in resolution timber, perpetration of conditioning, monitoring and evaluation of evolution, and application of each stage of evolution carried out. Participation or participation is principally a shape of active and voluntary involvement and participation, the excrescency and evolution of participation in the evolution process requires active trust and occasion in the evolution process, mindfulness and company and community responsibility for the significance of evolution which aims to ameliorate the quality of life. Keywords: village, Road Infrastrucute, Community, Participation, Development Planning